Effectiveness of rehabilitation programs in acute post-stroke: A systematic review - Gian Lisuari Adityasiwi; Irwan Budiono; Intan Zainafree; Chatila Maharani (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Introduction: The effectiveness of rehabilitation programs during the acute phase of stroke remain unclear. This study aimed to identify and analyze the forms of exercise education available for post-stroke patients based on a review of existing literature. Methods: This review was conducted in accordance with the preferred reporting items for systematic reviews and meta-analyses guidelines (PRISMA). This study included research articles related to rehabilitation programs for post-acute stroke patients that were published between 2019 and 2024. Literature searches were performed using PubMed, ScienceDirect, and Google Scholar. Results: Among the 10 eligible studies, effective programs involved collaboration among medical teams, caregivers, and families. Hospital-based training with early mobilization was often combined with home-based programs supported by technologies such as telehealth for remote monitoring to enhance mobility. In addition, the iron level assessments and vitamin supplementation were important to support the rehabilitation process for patients with acute stroke. Conclusion: Acute-phase rehabilitation has proven effective in enhancing physical recovery and function in stroke patients. However, methodological variations highlight the need for further research to develop region-specific protocols based on sociodemographic factors.